Naval history and maritime strategy collected essays - Hattendorf, John B. (Krieger Publishing, 2000)
This collection of 16 essays provides an insight into the interrelationship between naval history and maritime strategy. It examines the intellectual history of its development, the use of history within navies as a means of understanding strategy, and the history of navies.